2023
DOI: 10.3390/buildings13041034
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Shear Reinforcing of Reinforced Concrete Beams with Carbon Fiber Reinforced Polymer Grid-Strengthened Engineering Cementitious Composite

Abstract: This study investigates the shear behavior of reinforced concrete (RC) beams that have been strengthened using carbon fiber reinforced polymer (CFRP) grids with engineered cementitious composite (ECC) through finite element (FE) analysis. The analysis includes twelve simply supported and continuous beams strengthened with different parameters such as CFRP sheets, CFRP grid cross-sectional area, and CFRP grid size. To conduct the analysis, FE models of the RC beams were created and analyzed using ABAQUS softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…They concluded that the maximum drift can be lowered by 24% under in-plane actions if geo-fabric is used to strengthen the infill-frame interfaces. Sharifi Ghalehnoei et al [12] reported the outcomes of numerical modeling for RC beams strengthened by carbon-fiber-reinforced polymer grid-strengthened engineering cementitious composites. They compared analytical and numerical results and concluded that the difference between these approaches is not significant.…”
Section: Seismic Impact On Buildings: a Bird's Eye Viewmentioning
confidence: 99%
“…They concluded that the maximum drift can be lowered by 24% under in-plane actions if geo-fabric is used to strengthen the infill-frame interfaces. Sharifi Ghalehnoei et al [12] reported the outcomes of numerical modeling for RC beams strengthened by carbon-fiber-reinforced polymer grid-strengthened engineering cementitious composites. They compared analytical and numerical results and concluded that the difference between these approaches is not significant.…”
Section: Seismic Impact On Buildings: a Bird's Eye Viewmentioning
confidence: 99%